PENGARUH PENGGUNAAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VIII SEMESTER GENAP SMP NEGERI 2 PEKALONGAN - Fitriasari, Reni; Dewi, Tiara Anggia (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The purpose of this study was to determine the effect of using scramble learning models on integrated social studies learning outcomes of class VIII students in the even semester of SMP 2 Pekalongan in the academic year 2017/2018